2008
DOI: 10.1042/bsr20070027
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial non-syndromic sensorineural hearing loss: a clinical, audiological and pathological study from Italy, and revision of the literature

Abstract: Over the last decade, a number of distinct mutations in the mtDNA (mitochondrial DNA) have been found to be associated with both syndromic and non-syndromic forms of hearing impairment. Their real incidence as a cause of deafness is poorly understood and generally underestimated. Among the known mtDNA mutations, the A1555G mutation in the 12S gene has been identified to be one of the most common genetic cause of deafness, and it has been described to be both associated to non-syndromic progressive SNHL (sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 63 publications
1
21
0
2
Order By: Relevance
“…In another study by Silan et al (2011) among 64 Turkish prelingual hearing impaired subjects, one sporadic case was found to carry both a heterozygous c.35delG mutation in the GJB2 gene and the mitochondrial m.1555A>G mutation. GJB2 and GJB6 gene mutations were not present in any of the nine Italian idiopathic hearing loss subjects with the m.1555A>G mutation (Berrettini et al, 2008). No pathogenic mutations in the GJB2, GJB6 and SLC26A4 nuclear genes were observed along with the m.A1555G mutation in three unrelated idiopathic hearing loss subjects from the same region (Guaran et al, 2013).…”
Section: Factors Influencing Phenotypic Expression Of Hearing Loss Dumentioning
confidence: 89%
See 1 more Smart Citation
“…In another study by Silan et al (2011) among 64 Turkish prelingual hearing impaired subjects, one sporadic case was found to carry both a heterozygous c.35delG mutation in the GJB2 gene and the mitochondrial m.1555A>G mutation. GJB2 and GJB6 gene mutations were not present in any of the nine Italian idiopathic hearing loss subjects with the m.1555A>G mutation (Berrettini et al, 2008). No pathogenic mutations in the GJB2, GJB6 and SLC26A4 nuclear genes were observed along with the m.A1555G mutation in three unrelated idiopathic hearing loss subjects from the same region (Guaran et al, 2013).…”
Section: Factors Influencing Phenotypic Expression Of Hearing Loss Dumentioning
confidence: 89%
“…In a large Japanese pedigree with postlingual hearing loss, Matsunaga et al (2005) described variable phenotypic expression of hearing loss without exposure to aminoglycoside antibiotics. Berrettini et al (2008) studied nine Italian familial idiopathic hearing impaired subjects with the m.1555A>G mutation. Three of the nine subjects had a history of aminoglycoside antibiotic exposure.…”
Section: Factors Influencing Phenotypic Expression Of Hearing Loss Dumentioning
confidence: 99%
“…One of the pathogenic changes most frequently found in mtDNA, the A3243G mutation in the tRNA Leu(UUR) has been associated in some cases to diabetes plus deafness, although the same mutation was also reported in isolated deafness (17). Nonsyndromic hearing loss is a landmark in patients with the A1555G mutation in the 12S rRNA gene (18,19). In most patients harboring this mutation, hearing loss occurs after aminoglycoside treatment, but cases of deafness caused by A1555G without aminoglycoside exposure are not infrequent (19).…”
Section: Discussionmentioning
confidence: 99%
“…The patient did not show symptoms of noticeable hearing dysfunction before the age of 3 y, suggesting a progressive hearing loss to moderate deafness starting around this age. This progressive pattern is common in deafness due to mitochondrial dysfunction (18).…”
Section: Discussionmentioning
confidence: 99%
“…A number of racial populations over the world have been screened for the locus mtDNA m.1555A>G, again indicating markedly different mutation rates among different geographic or racial origins. In Caucasians living in Europe or America, the m.1555A>G mutation rates of sporadic patients are 0.6%-2.4% (Li et al, 2004;Berrettini et al, 2008;Konings et al, 2008;Rydzanicz et al, 2009); in Mongoloids living in East and Southeast Asia, a rate of 1.6%-8.56% was observed (Pandya et al, 1999;Oshima et al, 2001;Li et al, 2004;Guo et al, 2008;Wu et al, 2008), but it was not found among 122 and 221 nonsyndromic hearing loss subjects in Australia and North India, respectively (Ramsebner et al, 2007;Bhalla et al, 2009). Northwest China covers Shaanxi, Gansu, Qinghai, Ningxia, and Xinjiang.…”
Section: Introductionmentioning
confidence: 88%